Theory of mind and central coherence in eating disorders: two sides of the same coin? - Tapajoz Pereira de Sampaio, Fernanda (2013)
The aim of this study was to evaluate central coherence and theory of mind (ToM) and explore the relationships between these domains in patients with eating disorders (ED). ToM and central coherence were assessed in 72 women [24 with anorexia nervosa (AN), 24 with bulimia nervosa (BN) and 24 healthy controls (HC)]. The Reading the Mind in the Eyes (RME) and the Faux Pas Test (FPT) to measure ToM, and the copy strategy of the Rey–Osterrieth Complex Figure Test to assess central coherence were used. It was observed that patients with ED had a decrease in central coherence skills compared with the control group; that patients with anorexia had a poor performance on RME ToM task compared with BN patients and HCs, and also that these measures were related in both clinical groups. The statistically significant correlation between them suggests that the central coherence and ToM measures might involve common cognitive processes. These results provide a better understanding of the nature of the socio-cognitive deficits observed in patients with eating disorders.